1986
DOI: 10.1093/jn/116.12.2504
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bovine Growth Hormone Administration on Metabolism of Growing Hereford Heifers: Protein and Lipid Metabolism and Plasma Concentrations of Metabolites and Plasma Concentrations of Metabolites and Hormones

Abstract: The objectives were to determine the effects of daily injection of bovine growth hormone (bGH) on the metabolism of [1-14C]leucine and [1-14C]palmitate and on hormone and metabolite concentrations in growing Hereford heifers. The experimental design was a 28-d single reversal with two 14-d injection periods of placebo or bGH. Energy intake was restricted to a level slightly above maintenance. Injection of bGH did not affect circulating concentrations of glucose, beta-hydroxybutyrate, urea nitrogen, prolactin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
47
0
7

Year Published

1988
1988
2011
2011

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(62 citation statements)
references
References 36 publications
8
47
0
7
Order By: Relevance
“…Our current findings of the effects of ST on whole body accretion rates and amino acid oxidation are in accord with the majority of previous studies in animals and humans (4,6,17,24,25,29,37,38,45,46). However, less is known about the specific effects of ST on whole body proteolysis rates in the postabsorptive and postprandial states.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our current findings of the effects of ST on whole body accretion rates and amino acid oxidation are in accord with the majority of previous studies in animals and humans (4,6,17,24,25,29,37,38,45,46). However, less is known about the specific effects of ST on whole body proteolysis rates in the postabsorptive and postprandial states.…”
Section: Discussionsupporting
confidence: 91%
“…Less is known about its effects on protein degradation, particularly at the tissue level. The equivocal findings of the ST-induced effects on protein synthesis and protein degradation in previous studies may be due to different developmental stages of the subject population (i.e., growing vs. mature), species studied, nutrient status of the subject (i.e., fasted or fed), tissues analyzed, and length and/or mode of ST treatment (4,5,17,24,25,30,37,38,42,45).…”
mentioning
confidence: 89%
“…Eisemann et al (1989) sugeriram que o incremento da taxa fracional de síntese protéica propiciado pelo GH depende do mús-culo estudado. Elsasser et al (1998) observaram, em novilhos confinados, aumento de peso e maior taxa de deposição protéica nos músculos Rectus femoris e Tríceps brachii mediante o fornecimento de rbST (0,1 mg/kg/dia), sendo que o Supraspinatus, Psoas major e Semitendinosus não apresentaram alteração de peso ou mudança na taxa de deposição protéica em relação ao grupo controle.…”
Section: Resultsunclassified
“…An alternative theory is that more muscular cattle may also be leaner due to higher circulating growth hormone (GH) concentrations. Sejrsen et al (1983) and Johnsson and Hart (1985) demonstrated that a decrease in serum GH was associated with increased body fat in grain-fed heifers, while protein accretion was higher in animals with increased concentrations of GH (Eisemann et al, 1986). GH treatment also causes an increased lipolytic response to adrenaline in growing pigs and lactating cattle Novakofski et al, 1988;Sechen et al, 1990).…”
Section: Introductionmentioning
confidence: 99%